2021
DOI: 10.3390/socsci10020074
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Cluster Analysis of Human Value Priorities and Associations with Subjective Well-Being, Subjective General Health, Social Life, and Depression across Europe

Abstract: Human values are a central component in understanding individuals’ choices. Using the Schwartz’s Values instrument, this study aimed to identify patterns of human value priorities of 35,936 participants across 20 European countries and analyse their relations with subjective well-being (SWB), subjective general health (SGH), social life, and depression indices in Europe. A hierarchical cluster analysis of data from the seventh European Social Survey (ESS) round 7, based on the higher order dimensions of the Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 120 publications
0
2
0
Order By: Relevance
“…This may be due to the social‐focus and self‐protection motivation which underlines conservation values and may highlight concerns about safety and one's own fit within their environment. Alternatively, greater endorsement of the growth‐focussed values of self‐transcendence and openness to change have been found to negatively correlate with depression (Liu et al, 2021), although these findings are not consistent (Arens et al, 2022; España et al, in press; Heim et al, 2019; Leite et al, 2021; Zacharopoulos et al, 2021). For example, Hanel and Wolfradt (2016) found no associations between conservation values and depression, whereas Maercker et al (2015) found in a German sample a positive association between conformity and depression, but in a Chinese and a Russian sample a negative association.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the social‐focus and self‐protection motivation which underlines conservation values and may highlight concerns about safety and one's own fit within their environment. Alternatively, greater endorsement of the growth‐focussed values of self‐transcendence and openness to change have been found to negatively correlate with depression (Liu et al, 2021), although these findings are not consistent (Arens et al, 2022; España et al, in press; Heim et al, 2019; Leite et al, 2021; Zacharopoulos et al, 2021). For example, Hanel and Wolfradt (2016) found no associations between conservation values and depression, whereas Maercker et al (2015) found in a German sample a positive association between conformity and depression, but in a Chinese and a Russian sample a negative association.…”
Section: Introductionmentioning
confidence: 99%
“…For a better understanding of the choices that individuals make in various situations, human values are the main tools that mediate this process (Leite et al, 2021) and that motivate people's behavior (Gimenez & Tamajon, 2019;Zacharopoulos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%